Patients' Adherence to Healthy Behavior in Coronary Heart Disease: Risk Factor Management Among Jordanian Patients. Issue 6 (November 2015) - Mosleh, Sultan M.; Darawad, Muhammad
Abstract : Background: Poor adherence to risk factor management behaviors for coronary heart disease (CHD) patients increases the risk for a further cardiac event. There is a scarcity of literature about the level of adherence to risk factor management behaviors after CHD diagnosis in Jordan. Objective: The aim of this study was to explore which demographic, psychosocial, and clinical factors predict better adherence to risk factor management behaviors, particularly smoking cessation, physical activity, healthy diet, and medication adherence. In addition, we sought to explore the association of poor adherence to hospital readmission. Method: A cross-sectional survey was performed using a sample of 350 patients who visited the outpatient clinics in 4 hospitals in Jordan. Result: Data were obtained from 254 patients (response rate, 73%). Most were overweight (47.8%) or obese (28.5%), and 30% remained smokers after CHD diagnosis; 53 (21.5%) described themselves as ex-smokers. One-third of participants (88, 34.8%) performed regular walking exercise. Only 16% of participants reported that they had been instructed to perform regular activity. Stepwise multiple regressions revealed younger age and lower body mass index as independent predictors for more physical activity. Only 51 (20.9%) reported always following a low-fat dietary regimen, and participants who received dietary recommendation advice were significantly more likely to be on a healthy diet (odds ratio, 10.3; 95% confidence interval, 3.79–30.80; P < .001). Most of the participants (183, 72%) reported low medication adherence (score ⩽6), based on the Morisky scale, and only 5 (2%) reported a high adherence score (score = 8). Male gender and having chronic back pain were independent predictors for better medication adherence. About one-third of participants had been hospitalized for cardiac reason at last 2 times in the past 12 months. Rehospitalization was significantly more common among patients who were not following a dietary regimen (Mann-Whitney Z = −2.54, P = .011) or regular physical activity (Mann-Whitney Z = −3.60, P = .001) and in those who had more comorbidity diseases ( r = 0.34, P = .001). Conclusion: Our findings highlight poor adherence to secondary prevention behaviors among Jordanian CHD patients. Most participants did not adopt healthy behaviors in managing their CHD risk factors and they demonstrated a higher risk of hospital readmission. There is an urgent need for aggressive and targeted strategies to enhance adherence levels.